Pengaruh Profesionalisme Dan Komitmen Organisasi Terhadap Kinerja Pegawai Pada Kantor Inspektorat Kabupaten Sikka - Punga Ermita Lorensa; Walter Obon; Viktor Eko Transilvanus (Universitas Kristen Indonesia Toraja, 2023)
This research aimed to (1) determine the description of employee performance, professionalism and organizational commitment; and (2) analyze the effect of professionalism and organizational commitment on employee performance bith partially and simultaneously. The populations in this research were employees at the Inspectorate Office of Sikka Regency as many as 43 people. This research was conducted by census or saturated sampling due to limited population. Data were collected through questionnaires and analyzed through descriptive and inferential statistical methods, namely multiple linear regression. Hypothesis testing was done through the F-test and t-test. The results of descriptive analysis showed that the variables of employee performance, professionalism, and organizational commitment were categorizedas good. The results of the test statistic showed that partially the variables of professionalism and organizational commitment had a positive and significant effect on employee performance. The results of the T-test statistic showed that simultaneously, the professionalism and organizational commitment variables had a significant effect employee performance. The results of the determination analysis indicated that the two independent variables in this research could explain the fluctuation of employee performance at the Inspectorate Office of Sikka Regency by 25,1%